Customer’s Preference Among Four Types Of Restaurant / Nurul Aina Syahirah Mazlan - Mazlan, Nurul Aina Syahirah (Faculty of Business and Management, 2015)
Purpose-This undergraduate project aims to identify the most preferred type of restaurant in Dungun and to investigate the factors affecting the choice of restaurant in Dungun. Design/methodology/approach- The researcher collected 101 questionnaires from respondents who live in Dungun and analyzed by using frequency table and crosstab table. Findings- The results showed that most people preferred family restaurant as their preferred restaurants. Several factors were being analyzed and it was found that price saving, convenience, food assortment, food quality and perceived service quality had being the main concern. Practical implications- The results of this study suggested that more time are given for future research so that the researcher can seek for advice from experts. Originality/value- This study examined the type of restaurant that is most preferred by Dungun residents and what factors are influencing the choice of restaurant.